Muhammad Syahrurâ€™s View About of Ummiyatu Muhammad or Illiterate of Prophet Muhammad SAW - Ahmad Fakhruddin Fajrul Islam (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2021)
We have known that many Muslims consider his beloved prophet MuhammadSAW was illiterate. It was based on many evidences, Quran evidences, prophetic hadithevidences, and history evidences. However, this claim is still far from right because it hasbeen known that Prophet Muhammad had great intelligences. Before being a prophet orapostolate, Muhammad was known with many epithets among his people, such as al-amien.He was also wise man who could give solution when many tribes at Mecca want to fightjust to appoint of who has the right to put â€œhajar aswadâ€. Muhammad Syahrur, a modernIslamic scholar, denied that claim and tried to reveal the real meaning of ummi in Quran.Fortunately, Muhammad Syahrur did not writing about this topic only in his masterworkâ€œal-Kitab wa al-Qurâ€Ÿan; Qiraâ€Ÿah Muâ€Ÿashirahâ€. However, this topic is still an interestingtopic to be discussed.